IMPACTS AND CONSEQUENCES OF PROTAGONIST’S INNER CONFLICT IN THE BOY IN THE STRIPED PYJAMAS NOVEL BY JOHN BOYNE - Ningrum, Nur Hidayah Ayu Puspita; Margawati, Prayudias (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
This research examines the impact and the consequences of the protagonist's inner conflict in John Boyne's The Boy in the Striped Pyjamas through Karen Horney's theory of inner conflict and neuroticism. The research investigates how Bruno, the novel protagonist, deals with the impact and the consequences of his inner conflict on the storyline. The research explores how environmental changes significantly affect Bruno's development, identity, and interactions in the narrative. The problem begins with Bruno's move from Berlin to Out-With, a concentration camp for Nazi prisoners. Bruno sees firsthand the horrific environment, torture, and injustice of the new place. Each storyline has conflicts and obstacles that make Bruno's inner conflict worse. This research uses qualitative analysis, which is expected to produce an understanding of protagonist development when dealing with the impact of inner conflict on children in a social context. The impact of Bruno's inner conflict is significant, affecting various aspects of his life and actions, causing unhappiness and oppression. Bruno felt deeply unhappy and depressed, experiencing isolation and an inability to express his feelings, which often led to feelings of loneliness and alienation. This research aims to explore the impact of inner conflict on the psychological and social development of children, particularly in the context of historical trauma such as the Holocaust. The novel serves as a vehicle to discuss the effects of witnessing violence and trauma on children, which is a significant issue in psychology and child development studies. The protagonist, Bruno, experiences a range of emotions and behaviours as a result of his exposure to the harsh realities of a concentration camp, which reflects broader concerns about how such environments can affect a child's mental health and identity formation. This research also appears to be motivated by the desire to understand how individuals, especially children, cope with and are affected by their surroundings, particularly in extreme or adverse conditions.